Hospital-integrated Biobanking as a Service – The Interdisciplinary Bank of Biomaterials and Data Wuerzburg (ibdw). (23rd April 2018) - Geiger, Joerg; Both, Semira; Kircher, Stefan; Neumann, Michael; Rosenwald, Andreas; Jahns, Roland
The ibdw was established in 2011 as one of 5 centralised national biobanks in Germany within the framework of the governmental funding program "Nationale Biobank-Initiative". The ibdw is a joint core facility of both, the University Hospital and the Julius-Maximilians-University Würzburg and acts as a faculty-wide service provider of human biological material for medical research. From the outset main emphasis was placed on comprehensive automation and seamless integration of sample collection in clinical routine workflows thereby securing highest quality standards. The ibdw collects fluid and tissue samples in parallel from patients, based on a broad informed consent, hence not limiting future research use.